Diversidad biológica y conservación de los parques y jardines peruanos: un análisis bibliométrico - Aponte, Héctor (2025)
The biological diversity of parks and gardens provides different ecosystem services in the city. In order to protect it, it is important to have an idea of how much we know. The objective of this study was to bibliometrically analyze all the information on biological diversity and its conservation in Peruvian parks and gardens. For this, an information search was carried out in Scopus, Scielo, Science Direct and Google Scholar databases following the PRISMA methods; subsequently, the temporal trends of these publications were analyzed, as well as the thematic areas published, summarizing the information found. As a result, ninety scientific articles were identified, published between 2002 and 2024. The highest publication output occurred within the last nine years (p<0.05 for the Kruskal-Wallis test), with the most productive years being 2018, 2021, and 2023. Additionally, 57% of the documents were published in Peruvian journals. The most studied thematic areas were «Public spaces and conservation» and «Ornithology» and (with 32 and 18 articles respectively). Sixty-seven clusters were found among authors, of which only 4 have joint works (including only 10% of authors), suggesting an independent and sporadic advance of the research groups dedicated to the study of urban ecosystems. The need to continue studies in urban environments is discussed, particularly emphasizing those less studied thematic areas (in this case, herpetology and autoecology). Likewise, the need to establish policies for conserving biological diversity in these ecosystems is discussed; examples of good practices at the national and international levels are provided.